2019
DOI: 10.5398/tasj.2019.42.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Production Performance, Egg Quality, and Fecal Bacterial Population of Laying Ducks Fed Ration Supplemented by Bamboo Vinegar

Abstract: With the ban on the use of antibiotics in poultry feed, it is required to produce alternative substances to maintain poultry health and performance. The present study was carried out to investigate the effects of dietary supplementation at various levels of bamboo vinegar (BV) on performance, egg quality, and fecal bacterial population of laying ducks. One hundred and five 50-week-old crossbred laying ducks (Khaki Campbell × Native) were randomly allocated into five treatment groups, each with seven replicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Bobot badan merupakan salah satu sifat kuantitatif yang diwariskan namun penampakannya dipengaruhi oleh faktor lingkungan [11]. Bobot badan induk yang tinggi dapat menghasilkan produksi telur yang tinggi, serta dapat meningkatkan kualitas bibit yang dihasilkan [20]. Perbedaan bobot badan induk berpengaruh pada bobot telur yang dihasilkan, sehingga semakin beragam bobot induk yang berada pada satu kelompok itik, semakin beragam juga bobot telur yang dihasilkan.…”
Section: Metode Penelitianunclassified
“…Bobot badan merupakan salah satu sifat kuantitatif yang diwariskan namun penampakannya dipengaruhi oleh faktor lingkungan [11]. Bobot badan induk yang tinggi dapat menghasilkan produksi telur yang tinggi, serta dapat meningkatkan kualitas bibit yang dihasilkan [20]. Perbedaan bobot badan induk berpengaruh pada bobot telur yang dihasilkan, sehingga semakin beragam bobot induk yang berada pada satu kelompok itik, semakin beragam juga bobot telur yang dihasilkan.…”
Section: Metode Penelitianunclassified
“…(Rattanawut et al, 2017(Rattanawut et al, , 2018(Rattanawut et al, , 2021Suresh et al, 2020). In addition to modulating the balance of intestinal microflora and pathogens, bamboo vinegar can also enhance the nutrient digestibility of gut through improving the maturation and development of intestines (e.g., increasing the villus height and area, epithelial cell area and cell mitosis), and increasing the secretion of endogenous enzymes (Deng et al, 2013;Rattanawut et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that it may enhance immunity and accelerate growth of domestic animals (i.e., pigs, ducks, and chickens) through adjusting gut microflora (Samanya and Yamauchi, 2002;Watarai and Tana, 2005;Wang et al, 2012;Huo et al, 2016;Rattanawut et al, 2018Rattanawut et al, , 2019Yu et al, 2018;Schmidt et al, 2019), to the best of our knowledge, the impact of BVC on gut microflora remains unknown in commercial fish species. In addition, it has been suggested that intestinal morphological characteristics are closely related to nutrition uptake and health of an animal (Kelly and Coutts, 2000); however, whether the intestinal morphology of commercial fish species could be affected by dietary BVC supplementation awaits exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 21 ] stated that the egg production of ducks was exacerbated mainly by the infiltration of pathogenic bacteria such as Salmonella enterica. Hence, the provision of ingredients could reduce pathogenic bacteria to improve the productive performance of laying ducks by optimizing the feed metabolism and thus supporting the availability of required nutrients for egg production [ 22 ]. Egg production obtained in this study was substantially lower than that in the experiment carried out by Rostini et al [ 4 ], who reported that the egg production of Alabio ducks ranged between 47% and 81%.…”
Section: Discussionmentioning
confidence: 99%